PERAN DIGITALISASI PEMBAYARAN QRIS DAN LAYANAN SHOPEEFOOD DALAM MENINGKATKAN PENJUALAN PADA UMKM WIRING MIKIN ROLASIN - Diva Maharani; Zaenal Wafa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of digitalization through the Quick Response Code Indonesian Standard (QRIS) payment system and the ShopeeFood food delivery platform in increasing sales volume at Wiring Mikin Rolasin, a micro-business located in Yogyakarta. The research employed a descriptive qualitative method with a case study approach, collecting data through in-depth interviews, participant observation, and transaction documentation during the Field Work Practice (PKL) period. The results show that the implementation of QRIS significantly accelerated the transaction process, minimized change miscalculations, and automated daily financial records previously performed manually. Meanwhile. Wiring Mikin Rolasin’s integration with the ShopeeFood platform opened new sales channels beyond the physical geographic boundaries of the shop, with the number of online orders steadily increasing from 20 orders in the first week to 40 orders per week in the fourth week. The combination of these two technologies significantly impacted business performance. Average daily turnover increased by approximately 120% from Rp. 250,000 to Rp. 550,000 to Rp. 550,000-Rp. 1,000,000, while the number of daily transactions increases by almost 100%. This study concluded that the adoption of digital technologies such as QRIS and ShopeeFood has proven effective in modernizing operations, expanding market reach, and measurably increasing MSME revenue, even without requiring large capital or in-depth technical expertise.